SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN TEMPAT USAHA YANG STRATEGIS MENGGUNAKAN METODE WEIGHTED PRODUCT BERBASIS WEBSITE - Esih Kurniasih , Siti; Zein Vitadiar , Tanhella (Inovate, 2024)
Currently the internet is growing rapidly, making it a means of communication that continues to transform access to information, delivery of opinions, various forms of government and business for people around the word. However, the use of information system technology is still not very widespread in Kp. Pasar Sabut. In Kp. Pasar Sabut itself still does not have access to information to inform fecilities widely, so that people form outside the area do not know that there are business opportunities in Kp. Pasar Sabut. So that in reserching businee lacations, they still do it directly by visiting lacations one by one. This makes the selection of business lacations less effective, especially in Kp. Pasar Sabut has several places that require a lot of time. Then the solution of this problem can be solved by using the weighted product method, while the weighted product method requires multipcation to unify the attribute’s weight. The results of calculations using the weighted product method use the criteria of access, business opportunities, visibility, competition and rental costs. The final score is the result of the sum of the criteria multiplied by the weight value of the criteria and the highest score results will show the final value of the ranking. Keywords : place of business, information, weighted product.